A proposed management framework for water stewardship for small business in South Africa - Huxtable, Collette (Rhodes University, Faculty of Commerce, Rhodes Business School)
Climate change, severe weather events, population growth and, urbanisation are just a few of the leading causes contributing to the global water crisis. This global water crisis is negatively impacting the environment, and society, which includes business (large and small). Businesses are facing many water risks and challenges in their daily operations, such as water scarcity, water stress and water pollution, which are resulting in them being negatively impacted financially. For all business to overcome these risks and challenges which are negatively impacting their operations and to assist in protecting the scarce water resources left on the planet, the implementation of water stewardship practices will play a very important role. The literature has fallen short in addressing water stewardship frameworks and practices for small business. Through a sustainability lens underpinned by Natural Resource Based View Theory, this research study sets out to develop a water stewardship framework for implementation by small business to provide them with a competitive advantage. By reviewing the current literature and frameworks available to large business organisations, the insights gained allowed for a draft water stewardship framework to be developed from this literature, suitable for small business. This draft water stewardship framework for small business was used to gather further information on its suitability for small business, through an interview process. A qualitative interview process with seven small businesses in Makhanda (South Africa), allowed for data to be gathered and used to refine and adjust the draft water stewardship framework for small business. The findings from this research study show that small business do not have a global awareness of water problems and are not aware of the concept of water stewardship. Small business were very receptive to the draft water stewardship framework for small business and felt that its implementation would make a difference in saving scarce water resources and create a competitive advantage for them. The study concludes by recommending a water stewardship framework for small business (WSF4SB), who will play a leading role in fighting the water crisis. The implementation of the WSF4SB aims to provide small business with a sustainable competitive advantage by looking after scarce water resources ensuring there is sufficient water for current and future generations.
Keywords: Water-supply Management; Small business -- South Africa; Water-supply Economic aspects; Triple bottom line; Sustainable development reporting; Competitive advantage